Two-stage cultivation strategy for simultaneous increases in growth rate and lipid content of microalgae: a review - A. Aziz, Md Maniruzzaman; Kassim, Khairul Anuar; Shokravi, Zahra; Mohd Jakarni, Fauzan; Hong, Yuan Liu; Zaini, Nabilah; Lian, See Tan; Saiful Islam, A. B. M.; Shokravi, Hoofar (Elsevier, 2020)
The depletion of fossil fuels and the search for novel sustainable energy sources are challenges faced by countries throughout the world over the past few decades. Microalgae have received considerable interest as new oil sources for biofuel production. However, the enhancement of the lipid content in microalgae strains without decreasing the growth rate is a prerequisite for improving the economic viability of microalgae-derived biofuel production. The implementation of an appropriate cultivation strategy can increase both lipid accumulation and biomass production. One of the most-often suggested strategies is the cultivation of microalgae through two-stage cultivation strategy (TSCS). This paper aims to recapitulate the findings of recent studies and achievements in improving the lipid productivity and economic feasibility of TSCS. This article starts by highlighting different types of TSCS based on various stimuli. Afterwards, the most noteworthy culture parameters, including growth stage and initial cell density, are addressed. The existing experimental results show that lipid productivity can be enhanced by optimizing stress factor(s) and engineering processes. Moreover, it is reported that the modification or elimination of the pre-harvesting phase (which can be done by upgrading technical aspects and/or via stress induction strategies) can promote the economic feasibility of TSCSs.